Study the positive effects of “Whatsup” application in the educational process (Journal of the College of Education for Women, 2019)
Limited importance of research in a stand on the most important difficulties faced by both faculty and parents to communicate with each process to follow up on their children, and the analysis and inventory of the obstacles that hinder the educational process, and work to develop a vision of how to address these constraints and the important role of technology in the treatment of problems of the society so as to develop frameworks future to minimize the errors and the problems they face, and the development outlook for future generations in order to promote the educational level, especially that Iraq is going through a change in conditions in all sectors. Through the questionnaire, which includes questions set that was made on a sample of faculty was the average rate of the arithmetic for people who agree to use this technique by (3.1) By Likert scale, was also a questionnaire for Parents who agree to use this technique was the average rate arithmetic by (3.34) by Likert scale is a very good percentage.